2013
DOI: 10.4314/sokjvs.v11i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistant coagulase positive <i>Staphylococcus aureus</i> from chickens in Maiduguri,Nigeria

Abstract: Staphylococcus aureus is an Important agent of food poisoning. In many countries, it is the main bacterial organism responsible for diseases caused by exotoxin production and direct invasion with systemic dissemination. In poultry, S. aureus is associated with many clinical syndromes including tenosynovitis, omphalitis, femoral head necrosis, infected hock and stifle joints secondary to coccidiosis and "bumblefoot". A total of 100 tracheal swabs from 100 apparently healthy chickens from small holder flocks in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
25
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 21 publications
10
25
7
1
Order By: Relevance
“…The isolates showed highest resistance to ceftazidine (100%) followed by erythromycin (91.67%), ofloxacin (91.67%), cefoxitin (83.33%), cefuroxime (83.33%), cloxacillin (83.33%) and gentamicin (75%). The high resistance against erythromycin (91.67%) recorded in this study is in agreement with that of Suleiman et al (2013) and Geidam et al (2012b) who reported 100% and 85%, respectively. However, this is in contrast to that of Nworie et al (2013) who reported 65% resistance of MRSA against erythromycin.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The isolates showed highest resistance to ceftazidine (100%) followed by erythromycin (91.67%), ofloxacin (91.67%), cefoxitin (83.33%), cefuroxime (83.33%), cloxacillin (83.33%) and gentamicin (75%). The high resistance against erythromycin (91.67%) recorded in this study is in agreement with that of Suleiman et al (2013) and Geidam et al (2012b) who reported 100% and 85%, respectively. However, this is in contrast to that of Nworie et al (2013) who reported 65% resistance of MRSA against erythromycin.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the high vancomycin resistance recorded might be as a result of emergence of vancomycin resistance strains or the transmission of these bacteria by infected personnel to chickens in the study area which calls for a serious concern since vancomycin is currently one of the drugs of choice for the treatment of unresponsive infections caused by S. aureus. A high resistance against ofloxacin (91.67%) and gentamicin (75%) were also recorded in this study which was higher than the reports of Suleiman et al (2013) who reported 57.4% and 0% resistance against ofloxacin and gentamicin respectively, in Maiduguri. According to Suleiman et al (2013), sub-therapeutic administration of antibiotics as prophylactics, growth promoters or inaccurate dosages given to sick flocks by unqualified personnel may likely result in plasma concentrations that are inconsistent with the desired objectives which may result to resistance development as is the case in the present study.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…aureus is also an important agent of food poisoning because it can be found in water, dust, and air. In Nigeria and many other parts of the developing world, chickens live close to human dwellings and therefore play an important role in environmental contaminations; in addition, birds are vehicles for transmission of those pathogens to humans through the handling live birds or consumption of contaminated meat and other poultry products [5].…”
Section: Staphylococcus Aureus Spreadmentioning
confidence: 99%
“…These are one of the most prevalent bacteria in both human and animals (Persoons et al, 2009;Suleiman et al, 2013). Staphylococcus aureus is one of the most important pathogens colonizing the skin and mucus membranes of the nares in human and animals incriminated in different disease conditions ranging from minor skin infections, such as furunclosis and carbunclosis to severe and highly debilitating conditions such as pneumonia and endocarditis (Jensen and Lyon, 2009).…”
Section: Introductionmentioning
confidence: 99%